2017
DOI: 10.1038/s41598-017-08784-3
|View full text |Cite
|
Sign up to set email alerts
|

Reference miRNAs for colorectal cancer: analysis and verification of current data

Abstract: MicroRNAs (miRNAs) hold great promise in cancer research. The use of appropriate reference miRNAs for normalization of qPCR data is crucial for accurate expression analysis. We present here analysis and verification of current data, proposing a workflow strategy for identification of reference miRNAs in colorectal cancer (CRC). We performed a systematic review of studies aimed to identify stable reference miRNAs in CRC through high-throughput screening. Among the candidate miRNAs selected from the literature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…found that the plasma levels of miR‐423‐5p correlated inversely with CRC progression, including adenomas and polyps, suggesting its potential as a biomarker for CRC, particularly in the early stages . Finally, one of the four miRNAs we identified as reference for our analyses, miR‐345‐5p, has already been proposed as reference miRNA for CRC analyses in a plasma circulating setting …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…found that the plasma levels of miR‐423‐5p correlated inversely with CRC progression, including adenomas and polyps, suggesting its potential as a biomarker for CRC, particularly in the early stages . Finally, one of the four miRNAs we identified as reference for our analyses, miR‐345‐5p, has already been proposed as reference miRNA for CRC analyses in a plasma circulating setting …”
Section: Discussionmentioning
confidence: 64%
“…51 Finally, one of the four miRNAs we identified as reference for our analyses, miR-345-5p, has already been proposed as reference miRNA for CRC analyses in a plasma circulating setting. 52 As reviewed by Slaby et al, 53 many studies have examined the feasibility of using circulating miRNAs as biomarkers for the early detection of CRC, but in most cases there is minimal overlap in the identified miRNAs. In fact, there is variability among studies, and the reproducibility of results can be influenced by multiple factors, including the number of samples and the number of miRNA tested, different experimental procedures and methods, normalization approaches, differences in patient populations and instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNA), small noncoding RNAs, bind to the 3' untranslated region (3' UTR) of their messenger RNA (mRNA) targets for posttranscriptional gene regulation that inhibits translation or mRNA degradation [9][10][11]. Thus, changing the expression patterns of either oncogenes or tumor suppressor genes via miRNAs plays an important role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Danese et al, the combination of hsa-miR-1228 and hsa-miR-520d was identified as the best reference to normalize RT-qPCR miRNA analysis in colorectal adenocarcinoma from exosome, plasma, and tissue samples. These two miRNAs were selected among six potential reference genes (hsa-miR-191, hsa-miR-193a, hsa-miR-345, hsa-miR-520d, and hsa-miR-1228) based on their stability assessed trough both Norm-Finder and BestKeeper algorithms [100]. Song et al, in a study on serum miRNAs from gastric cancer patients, have identified hsa-miR-16 and hsa-miR-93 as reference genes.…”
Section: Normalization On Endogenous Reference Genesmentioning
confidence: 99%